Effect of perioperative thermal control on postoperative rehabilitation in patients undergoing laparoscopic resection for colorectal malignancy - Miao Wang; Yuanfu Zhang; Yumei Xiang (Medicine, 2026)
This study examines the association between receipt of a multicomponent enhanced perioperative warming strategy and short-term recovery after elective laparoscopic colorectal cancer resection. This single-center retrospective cohort study included adults treated from January 2024 through December 2025. The warming strategy was determined by the protocol documented in anesthesia and nursing records rather than by random allocation. Propensity scores were estimated using pre-exposure variables, and patients were matched 1:1 without replacement. Balance was evaluated using absolute standardized mean differences. Matched-pair methods were used for outcome analyses, and adjusted sensitivity models addressed selected perioperative recovery factors. In the synthetic teaching dataset, 184 records were screened, 146 patients met eligibility criteria, and 100 patients (50 matched pairs) were analyzed. Enhanced warming was associated with less intraoperative hypothermia (12.0% vs 56.0%; exact McNemar P < .001) and a significant group-by-time temperature interaction ( P < .001). Median time to first flatus was 58.5 [48.0, 67.0] vs 69.5 [62.0, 80.0] hours (paired P < .001). Oral intake, ambulation, and discharge also occurred earlier, and these associations persisted in adjusted sensitivity analyses. Postoperative shivering was numerically lower (4.0% vs 16.0%) but was not statistically significant in the matched analysis (exact McNemar P = .109; Fisher exact P = .092). Lower neutrophil proportions were observed on postoperative days 1 and 3; the biomarker analyses were exploratory. In this retrospective matched cohort, receipt of a multicomponent enhanced perioperative warming strategy was associated with improved maintenance of normothermia and earlier short-term gastrointestinal recovery. Residual confounding, treatment-selection bias, and the bundled nature of the intervention preclude causal attribution to warming itself or to any single component. The inflammatory-marker findings should be considered exploratory.